Arsenic and arsenate detection with anodic stripping voltammetry technique using boron-doped diamond modified by platinum. Issue 1 (February 2020) - Sitorus, R; Saefumillah, A; Ivandini, T A
Abstract: High homogeneity and stability of platinum particles modified at boron-doped diamond (BDD) electrode was successfully performed using chemical seeding, followed by electrodeposition technique. The platinum particles on the surface of BDD characterized using Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy (SEM-EDS) showed that the coverage of Pt particles was 1.54 % on the BDD surface. These modified electrodes were used for As 3+ and As 5+ sensors using the anodic stripping voltammetry technique in 0.1 M phosphate buffer solution pH 6. Prior to the detection, pretreatment was required by the addition of 0.1 M NaBH4 to change As 5+ to As 3+ . The optimum parameters were at a deposition potential of -500 mV, a deposition time of 150 s, and a scan rate of 200 mV/s. The voltammograms were linear for As 3+ and As 5+ (R 2 = 0.9797 and 0.9903, respectively) in the concentration range of 0 to 100 ppb. Estimated detection limits of 16.50 and 8.19 ppb for AS 3+ and As 5+ were achieved, respectively, suggesting that the method is promising for the specification detection of As 3+ and As 5+ .